Epistemology of ignorance: the contribution of philosophy to the science-policy interface of marine biosecurity - Schwenkenbecher, Anne; Hewitt, Chad L.; Heesen, Remco; Campbell, Marnie L.; Fritsch, Oliver; Knight, Andrew T.; Nash, Erin (Frontiers in Marine Science, 2023)
Marine ecosystems are under increasing pressure from human activity, yet successful management relies on knowledge. The evidence-based policy (EBP) approach has been promoted on the grounds that it provides greater transparency and consistency by relying on ‘high quality’ information. However, EBP also creates epistemic responsibilities. Decision-making where limited or no empirical evidence exists, such as is often the case in marine systems, creates epistemic obligations for new information acquisition. We argue that philosophical approaches can inform the science-policy interface. Using marine biosecurity examples, we specifically examine the epistemic challenges in the acquisition and acceptance of evidence to inform policy, discussing epistemic due care and biases in consideration of evidence.